The Role of Demographic Factors in Tourists’ Sustainability Consciousness, Sustainable Tourism Awareness and Purchasing Behavior - Gözde Özdemir Uçgun; Muhammed Talha Narcı (Journal of Tourismology)
The aim of this research is to investigate the role of demographic factors on tourists’ sustainability consciousness, awareness of sustainable tourism and purchasing behavior. The importance of the study is that it examines the subject in a holistic manner and develops suggestions based on study findings. It investigated whether variables such as age, gender, income level, and educational status have an effect on the perspective of tourists, on sustainable tourism practices in accommodation facilities, and on purchasing behaviors. The issue of sustainability, which is evaluated in terms of consumption and waste of natural resources, food, and goods in the literature was investigated within the scope of a tourists’ perspective and perception in this study and thus data that can shed light on the sector stakeholders were obtained. In the research, data were collected with the help of questionnaires and 386 valid responses were received to the questionnaires. The obtained data were analyzed with SPSS 26.0 and AMOS programs. The research findings and the literature were compared, and various suggestions are presented. Accordingly, the aging of individuals, in other words their maturation and the increase in education levels raise both sustainability consciousness and sustainable tourism awareness. However, it was determined that these variables do not have a statistically significant effect on the purchasing behavior of tourists.